BIM-Powered Energy Efficiency and Life-Cycle Cost Analyses for Greener Design - Balo, Figen; Sua, Lütfü S.; Boydak, Hazal (CRC Press, 2024)
Sustainable and green constructions have acquired importance in recent years due to increasing environmental concerns and the rapid depletion of fossil energy sources. Building Information Modeling (BIM) is a strategy that can analyze building performance by modeling buildings at an early stage. Different programs based on BIM are used in performance analysis. Green Building Studio is one of the prominent programs because of the approximity of the results obtained. It can make the performance evaluation procedure much simpler, especially with its feature of integrating and extracting the desired materials into the design of an existing or newly built building. In this study, a cafe in Tekirdag city of Turkey was modeled by BIM-powered Autodesk Revit. The main contribution of this study is creating scenario groups with different alternative types according to the sandwich wall structure through different construction, insulation, and roof materials of the modeled café. All types were created by detailing all facades of each scenario group for four different facades, all without green walls, all with green walls, and only one facade with green walls. Café is visualized with Lumion software. The energy performances of all types have been evaluated comparatively with Green Building Studio. The effect of adding green walls to the facades of a building on energy efficiency based on the directions was evaluated. © 2024 Taylor & Francis Group, LLC.